Implicit Compliments in the Performance of Iraqi Arabic Speakers (مجلة ديالى للبحوث الانسانية, 2022)
The current research study tackles the speech act of implicit complimenting from a pragmatic perspective among Iraqi Arabic native speakers. The choice of this topic for detailed investigation is ascribed to the fact that it has not received due attention as far as Iraqi Arabic is concerned. Being an expressive speech act, like request, apology, etc.implicit complimenting is commonly used in everyday discourse since interlocutors usually pay and receive compliments in their daily interaction. The current study comprises two parts: A theoretical framework which unveils definitions of compliments, types, salient features of compliments, in addition to their syntactic and pragmatic structures. The second part constitutes the practical part of the topic which is in the form of tape – recorded conversations conducted with students of the third and fourth grades at the Arabic Department / Wasit University/ Iraq. These students have been chosen since they are supposed to be more proficient than other grades in the use of language functions. Results have shown that Iraqi students still need much more pragmatic instruction concerning the speech act of implicit complimenting to be able to use it properly and efficiently in their everyday communication. The study has also found that implicit compliments seldom take place in conversations